Probiotic Potential of Lactic Acid Bacteria on Feed Efficiency, Weight and Carcass Percentage in Ducks - Chandra, Evania Haris; Lokapirnasari, Widya Paramita; Hidanah, Sri; Al-Arif, Muhammad Anam; Yuniarti, Wiwik Misaco; Luqman, Epy Muhammad (Jurnal Medik Veteriner, 2022)
The aim of the study was to determine the effect of the use of probiotic lactic acid bacteria (Lactobacillus acidophilus, Lactobacillus casei, Lactococcus lactis, and Bifidobacterium sp) on feed efficiency, carcass weight and carcass percentage in broiler ducks. Probiotics lactic acid bacteria produce bacteriocins and organic acids that inhibit the growth of pathogenic microbes in the digestive tract of poultry, so that the intestinal villi of broiler ducks are healthy. Besides that, probiotics are able to reduce cholesterol levels in meat when consumed by humans and can improve health. This study used 48 peking ducks. The probiotics of Lactic Acid Bacteria used were a concentration of 1.2 x 108 CFU/ml. In this study there were four different treatments, namely P0 (without probiotics), P1 (given 1 ml probiotics/liter drinking water), P2 (given 2 ml probiotics/liter drinking water) and P3 (given 3 ml probiotics/liter of drinking water). The results of the feed efficiency study showed that there was a significant difference (p<0.05) in the P0, P1, P2 and P3 treatments. The highest feed efficiency was at P3 (33.81%) while the lowest was P0 (30.84%). The results of the study on carcass weight indicated that the probiotics tended to be higher than those who were not given probiotics but statistically not significantly different (p>0.05). The highest carcass weight was P3 (1749.92 g) and the lowest was P0 (1709.25 g). The results of the study on the percentage of carcass weight showed a significant difference (p<0.05) in both P0, P1, P2 and P3 treatments. The highest percentage of carcass weight was at P3 (64.60%) and the lowest was P0 (60.96%). It can be concluded that the administration of probiotics lactic acid bacteria (Lactobacillus acidophilus, Lactobacillus casei, Lactococcus lactis, and Bifidobacterium sp) at a dose of 1 ml/liter of drinking water, 2 ml/liter of drinking water and 3 ml/liter of drinking water can affect feed efficiency and the percentage of duck carcasses. but has no effect on the carcass weight of broiler ducks.